Short Term Outcome of Preterm Neonates Required Mechanical Ventilation - Mannan, Md Abdul; Jahan, Nasim; Iqbal, Shahed; Ferdous, Navila; Dey, Subir; Farhana, Tashmin; Nazma, Nondita (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: Since its inception, the neonatal mechanical ventilator has been considered an essential tool for managing preterm neonates with Respiratory Distress Syndrome (RDS) and is still regarded as an integral component in the neonatal respiratory care continuum. Mechanical ventilation of newborn has been practiced for several years with several advances made in the way. As compared to the western world and neighboring countries, neonatal ventilation in our country is still in its infancy. To analyze the common indications and outcome of preterm neonates required mechanical ventilation. Methods: This was a retrospective observational study conducted on preterm neonates required mechanical ventilation over a period of 12 months (July 2013 to June 2014). Results: A total of 50 neonates were mechanically ventilated during the study period of which 68% (n=34) survived. The survival rate was higher (77%) in 34- <37 weeks Gestational Age (GA) group and gradually declined in 30- <34 weeks (71%) & 27- <30 weeks (56%) GA. The neonates with Birth Weight (BW) ? 2500gm were higher survivals which was 100% and lower in 1500-2499gm (81%), 1000-1499gm (68%) and 800-999gm (33%) BW groups. Inborn neonates (68%) showed marginally higher survivals than outborn (66%) and also more survivals observed in preterm baby girls (72%) than boys (65%). RDS (62%) was the commonest indication for ventilation followed by Neonatal Sepsis (14%), Perinatal Asphyxia (PNA-10%), Congenital Pneumonia (8%) and Pneumothorax (6%). And found higher survivals in RDS (77%) than other indications which were in Pneumothorax (66%), PNA (60%), Sepsis (57%) and Pneumonia (50%). RDS (n=31) with surfactant therapy (n=14) recovered earlier <7 days (71.43%) than non surfactant therapy neonates (n=17), they required prolonged ventilator support over 7days (82.35%). Conclusions: Mechanical ventilation reduces the neonatal mortality, hence facilities for neonatal ventilation should be included in the regional and central hospitals providing intensive care for neonates. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 9-13